Fathers of Deaf and Hard-of-Hearing Infants and Toddlers – Experiences, Needs, and Challenges. (28th December 2018) - Hintermair, Manfred; Sarimski, Klaus
Abstract: Studies on fathers with deaf and hard-of-hearing (DHH) children are quite rare in deaf education; if they are conducted, they narrowly focus on preschool-age or school-age children. The study reported here presents data from a survey on 92 fathers of very young DHH children with a mean age of 26 months. Questionnaires were used to measure the impact of children's hearing loss on parenting, the frequency of fathers' participation in early intervention appointments, and the level of fathers' involvement in daily care as well as in early intervention activities. Furthermore, information on fathers' perceived support from early intervention agencies, general self-efficacy, parenting self-efficacy, and marital satisfaction was assessed. The results confirmed data from other studies addressing fathers with children who have a disability. In particular, a strong relationship between parenting self-efficacy, perceived support by early intervention agencies and activities, and impact of child's hearing loss on parenting became evident. This indicates the importance of participation and involvement of fathers in early intervention activities; therefore, early intervention services must enable fathers to participate as much as possible in sessions.